2015
DOI: 10.3390/su70810210
|View full text |Cite
|
Sign up to set email alerts
|

The Spread of Knowledge Management in SMEs: A Scenario in Evolution

Abstract: This paper deals with knowledge management (KM) in small and medium enterprises (SMEs). Through a literature review, three research questions have been identified concerning the barriers hindering the spread of KM practices in SMEs, the main knowledge management systems (KMSs) adopted by SMEs and the impact of the use of KM practices on SME performance. The research questions were subsequently addressed through a field analysis conducted on a sample of SMEs. The empirical evidence highlights that the scenario … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 117 publications
(108 reference statements)
1
56
1
3
Order By: Relevance
“…Literature on sustainability management studies have been highlighted that knowledge management [2][3][4], business strategy [5,6], and organizational learning [7,8] are considered as vital indicators of firm sustainability performance improvement. Some researchers confirm that knowledge management and its output, organizational knowledge, are antecedents of organizational learning [9,10] and company business strategy [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Literature on sustainability management studies have been highlighted that knowledge management [2][3][4], business strategy [5,6], and organizational learning [7,8] are considered as vital indicators of firm sustainability performance improvement. Some researchers confirm that knowledge management and its output, organizational knowledge, are antecedents of organizational learning [9,10] and company business strategy [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have revealed that knowledge creation and human resources are still low, but the application of knowledge creation can improve the competitiveness and performance of SMEs (Cerchione et al, 2015). Knowledge creation and technology mastery in SMEs are different from the theory of knowledge creation frequently encountered in big companies.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The use of information technology plays a very big role, especially when supported by government policies that support the technology sector (Raf, 2000). Cerchione et al (2015) state that the use of IT provides a support for the management strategies associated with the aspect of communication, access to information, decisionmaking, data management and knowledge management in an organization. IT can be a strategic force and an organizational tool that benefits the promotional aspects and competitiveness (Carr, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…ICT made it possible to improve drastically the economic value of the large stock of knowledge available in the system and to reduce its costs of absorption (Antonelli, Geuna, Steinmueller, 2000). Cerchione Esposito and Spadaro (2015) document the wide range of specific computer applications that enable to widen the search in the stock of external knowledge available in the system. The use of the new ICT based techniques enables to overcome the classical separation of scientific and technological knowledge.…”
Section: Ict: Knowledge Spillovers and Absorption Costsmentioning
confidence: 99%